Carrot (Daucus carota L.) Seed Germination Was Promoted by Hydro-Electro Hybrid Priming Through Regulating the Accumulation of Proteins Involved in Carbohydrate and Protein Metabolism - Zhao, Shuo; Zou, Hao; Jia, Yingjie; Pan, Xueqin; Huang, Danfeng (Frontiers in Plant Science, 2022)
Asynchronized and nonuniform seed germination is causing obstacles to the large-scale cultivation of carrot (Daucus carota L.). In the present study, the combination of high voltage electrostatic field treatment (EF) with hydropriming (HYD), namely hydro-electro hybrid priming (HEHP), significantly improved all germination indicators of carrot seeds, and the promoting effect was superior to that of the HYD treatment. A tandem mass tags (TMT)-based proteomic analysis identified 4936 proteins from the seeds, and the maximum number of differentially abundant proteins (DAPs) appeared between CK and HEHP. KEGG analysis revealed that the upregulated DAPs were mainly enriched in the pathways related to protein synthesis and degradation such as “ribosome” and “proteasome”, while the downregulated DAPs were mainly enriched in photosynthesis-related pathways. Furthermore, the maximum DAPs were annotated in carbohydrate metabolism. Some proteins identified as key enzymes of the glyoxylate cycle, the tricarboxylate cycle, glycolysis and the pentose phosphate pathway showed enhanced abundance in priming treatments. The activities of several key enzymes involved in carbohydrate metabolism were also enhanced by the priming treatments, especially the HEHP treatment. Real-time quantitative PCR (qRT-PCR) analysis revealed that the effect of priming is mainly reflected before sowing. In conclusion, the optimal effect of HEHP is to regulate the synthesis and degradation of proteins in seeds to meet the requirements of germination and initiate the utilization of seed storage reserves and respiratory metabolism. The present work expanded the understanding of the response mechanism of carrot seed germination to priming and the biological effects of high voltage electrostatic field.